Differentiating Responders and Non-responders to rTMS Treatment for Disorder of Consciousness Using EEG After-Effects - He, Renhong; Fan, Jianzhong; Wang, Huijuan; Zhong, Yuhua; Ma, Jianhua (Frontiers in Neurology, 2020)
Background: It is controversial whether repetitive transcranial magnetic stimulation (rTMS) has potential benefits in improving the awareness of patients with disorder of consciousness (DOC) is still up for debate. We hypothesized that rTMS could improve the consciousness only in DOC patients who have measurable brain responses to rTMS. Objective: In this study, we aimed to investigate the EEG after-effects induced by rTMS in DOC patients and attempted to propose a prediction algorithm to discriminate between DOC patients who would respond to rTMS treatment from those who would not. Methods: Twenty-five DOC patients were enrolled in this study. Over four weeks, each patient received 20 sessions of 20 Hz rTMS that was applied over the left dorsolateral prefrontal cortex (DLPFC). For each patient, resting-state EEG was recorded before and immediately after one session of rTMS to assess the neurophysiologic modification induced by rTMS. The coma recovery scale revised (CRS-R) was used to define responders with an improved consciousness. Results: Of the 25 DOC patients, 10 patients regained improved consciousness and were classified as responders. The responders were characterized by more preserved alpha power and a significant reduction of delta power induced by rTMS. The analysis of receiver operating characteristic (ROC) curves showed that the algorithm calculated from the relative alpha power and the relative delta power had a high accuracy in identifying DOC patients who were responders. Conclusions: DOC patients who had more preserved alpha power and a significant reduction in the delta band that was induced by rTMS are likely to regain an improved consciousness, which provides an analysis to identify DOC patients who may obtain benefits regarding therapeutic consciousnessbenefits from rTMS.